The mGlu5 receptor antagonist MPEP activates specific stress-related brain regions and lacks neurotoxic effects of the NMDA receptor antagonist MK-801: significance for the use as anxiolytic/antidepressant drug - Inta, Dragos; Gass, Peter (Neuropharmacology, 2012)
Glutamatergic agents have been conceptualized as powerful, fast-acting alternatives to monoaminergic-based antidepressants. NMDA receptor antagonists such as ketamine or MK-801 are therapeutically effective, but their clinical use is hampered by psychotomimetic effects, accompanied by neurotoxicity in the retrosplenial and cingulate cortex. Antagonists of metabotropic mGlu5 receptors like MPEP elicit both robust antidepressant and anxiolytic effects; however, the underlying mechanisms are yet unknown. mGlu5 receptors closely interact with NMDA receptors, but whether MPEP induces neurotoxicity similar to NMDA receptor antagonists has not been elucidated. We show here using c-Fos brain mapping that MPEP administration results in a restricted activation of distinct stress-related brain areas, including the bed nucleus of stria terminalis (BNST), central nucleus of the amygdala, and paraventricular nucleus of the hypothalamus (PVNH), in a pattern similar to that induced by classical antidepressants and anxiolytics. Unlike the NMDA antagonist MK-801, MPEP does not injure the adult retrosplenial cortex, in which it fails to induce heat shock protein 70 (Hsp70). Moreover, MPEP does not elicit to the same extent as MK-801 apoptosis in cortical areas at perinatal stages, as revealed by caspase 3 expression. These data identify new cellular targets for the anxiolytic and antidepressant effect of MPEP, indicating also in addition that in contrast to MK-801, it lacks the cortical neurotoxicity associated with psychotomimetic side-effects.